Risk group assignment differs for children and adults 1–45 yr with acute lymphoblastic leukemia treated by the NOPHO ALL‐2008 protocol. (2nd April 2013) - Toft, Nina; Birgens, Henrik; Abrahamsson, Jonas; Bernell, Per; Griškevičius, Laimonas; Hallböök, Helene; Heyman, Mats; Holm, Mette Skov; Hulegårdh, Erik; Klausen, Tobias Wirenfeldt; Marquart, Hanne V.; Jónsson, Ólafur Gísli; et al.
Abstract Background The prognosis of acute lymphoblastic leukemia is poorer in adults than in children. Studies have indicated that young adults benefit from pediatric treatment, although no upper age limit has been defined. Design and methods We analyzed 749 patients aged 1–45 yr treated by the NOPHO ALL‐2008 protocol. Minimal residual disease (MRD) on days 29 and 79, immunophenotype, white blood cell count (WBC), and cytogenetics were used to stratify patients to standard‐, intermediate‐, or high‐risk treatment with or without hematopoietic stem cell transplantation. Results Adults aged 18–45 had significantly lower WBCs at diagnosis compared with children aged 1–9 and 10–17 yr, but significantly more adults were stratified to high‐risk chemotherapy (8%, 14%, 17%; P < 0.0001) or high‐risk chemotherapy with transplantation (4%, 13%, 19%; P < 0.0001). This age‐dependent skewing of risk grouping reflected more T‐ALL (11%, 27%, 33%, P < 0.0001), poorer MRD response day 29 (MRD < 0.1%: 75%, 61%, 52%; P < 0.0001), and more MLL gene rearrangements (3%, 3%, 10%; P = 0.005) in older patients. Conclusions Even if identical diagnostics, treatment, and risk stratification are implemented, more adults will be stratified to high‐risk therapy, which should be considered when comparing pediatric and adult outcomes.